Predictive value of IBI for acute kidney injury with contrast after PCI in patients with ST-segment elevation myocardial infarction - Ge, Wenjun; Zhang, Ying; Ge, Song; Chen, Mei; Xu, Yang (Frontiers in Cardiovascular Medicine, 2025)
BackgroundContrast-induced acute kidney injury (CI-AKI) is a common complication in patients with ST-segment elevation myocardial infarction (STEMI) and is associated with an inflammatory response. Inflammatory burden index (IBI) is a novel inflammatory marker, and the relationship between IBI and CI-AKI in STEMI patients is currently unknown. The aim of this study was to investigate the effect of IBI on CI-AKI after percutaneous coronary intervention (PCI) in STEMI patients.MethodsThis was a single-center retrospective observational study consecutively enrolling patients diagnosed with STEMI and successful PCI between August 2022 and December 2024. Logistic regression analysis was used to identify risk factors associated with CI-AKI. Restricted cubic spline (RCS) was used to explore the dose-response relationship between IBI and CI-AKI. The predictive effectiveness of the models was assessed by the net reclassification index (NRI) and the integrated discriminant improvement index (IDI).ResultsA total of 647 patients were included in this study and the incidence of CI-AKI during hospitalization was 78 (12.1%). After adjusting for possible confounding factors, the result showed that IBI > 18.89 (OR = 2.418, 95% CI: 1.331–4.392) was an independent factor for CI-AKI in STEMI patients. RCS results suggested that there was a non-linear dose-response relationship between IBI and CI-AKI. After integrating IBI, the ability of the new model to predict CI-AKI in STEMI patients was significantly improved (NRI = 0.315, IDI = 0.019, P < 0.05).ConclusionElevated IBI is an independent risk factor for CI-AKI after PCI in STEMI patients, and there is a non-linear dose-response relationship between IBI and CI-AKI. Integrating IBI can improve the risk stratification of STEMI patients regarding CI-AKI.